If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x = x + 25 Reorder the terms: 3x = 25 + x Solving 3x = 25 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 3x + -1x = 25 + x + -1x Combine like terms: 3x + -1x = 2x 2x = 25 + x + -1x Combine like terms: x + -1x = 0 2x = 25 + 0 2x = 25 Divide each side by '2'. x = 12.5 Simplifying x = 12.5
| x^2-6xy+5y^2-x+5y=0 | | (X-3/7)=2/3(3/2x-9/14) | | .07x+x=5000 | | 1.07x=5000 | | 17/7x=1/2 | | 4/7×x=40 | | -6x-y=-2 | | 200x^2=100 | | 7-3(2y+1)=16 | | 1.75x-0.75y=0 | | 5x^2+5x+5=100 | | 5x^2+6x+6=20 | | 4x+15y=31 | | 7x+6y=41 | | 3(0)-9(1/3)=15 | | 6x-5y=41 | | 3(3)-9(3)=15 | | 5x+2y=1.5 | | 4x-2y=-0.1 | | 1/(1-tanx) | | -9a+8a+36=11 | | 8.99x+4.6y-5.75xy=0 | | 8x+5.5y+6.25xy=0 | | 8x+5.5y-6.25xy=0 | | -9+2y=-66 | | -4x+3y=44 | | n!/(n-2)!=132 | | 3x^2+9=2x+1 | | 3600-x/3 | | (t-1)squared+(t-8)squared=45 | | 4cos(3x)+3=5 | | 4x+4y=4(x+y) |